Hubungan Tingkat Pengetahuan Gizi, Aktivitas Fisik, Dan Pola Konsumsi Pangan Dengan Status Gizi Pada Pekerja (Studi di Pabrik Tahu Sumber Makmur Banjarbaru) - Aulia Rostia Rini; Ermina Syainah; Rusmini Yanti; Nurhamidi Nurhamidi (CV. Wadah Publikasi Cendekia, 2023)
Background: Riskesdas 2018 in South Kalimantan showed the prevalence of nutritional status in the underweight category was 10.72%, the normal category was 56.34%, the overweight category was 13.42%, and the obesity category was 18.63%. Meanwhile, in Banjarbaru, the prevalence of underweight nutrition in the 19-65 year age group was 13.40%, the normal category was 59.57%, overweight was 13.95%, and the prevalence of obesity was 20.04%. Undernutrition, overnutrition, and obesity in Banjarbaru are above the provincial prevalence. This shows that the nutritional status of adults aged 19-65 years is still a problem in Banjarbaru. The nutritional problem for workers at the Sumber Makmur Tofu Factory Banjarbaru is malnutrition, which is 86.7%. Objective: To determine the relationship between the level of nutritional knowledge, physical activity, and food consumption patterns with the nutritional status of the workers of the Sumber Makmur Tofu Factory Banjarbaru. Method: Analytical observation with Cross Sectional design. A sample of 15 people was taken by means of saturated sampling. The research data was taken using a questionnaire. Data analysis used Spearman Rank correlation test =0.05. Results: Shows the level of knowledge of malnutrition (93.3%) with a significant (p value) 0.012, high physical activity (93.3%) with a significant (p value) 0.711, a pattern of poor food consumption (93.3%%) with a significant (p value) 0.012, and more workers have underweight nutritional status (86.7%). Conclusion: There was a significant relationship between the level of nutritional knowledge and nutritional status, there was no relationship between physical activity and nutritional status, and there was a significant relationship between food consumption patterns and nutritional status.